2019
DOI: 10.12659/msm.918806
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and Qualitative Evaluation of Breast Cancer Prognosis: A Sonographic Elastography Study

Abstract: BackgroundBreast cancer is one of the most commonly diagnosed cancers in women worldwide, and sonographic elastography has previously demonstrated good performance in detecting breast malignancies. However, the exact relationship between elastographic measures and clinical prognostic factors is still not well understood. Thus, the aim of this study was to evaluate any associations between major clinical prognostic factors and strain elastography and to validate the diagnostic value of elastography in breast ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
4
5
0
Order By: Relevance
“… 43 , 44 In a murine model, Chamming’s et al 40 confirmed a negative correlation between stiffness and necrosis and a positive correlation between stiffness and fibrosis. However, the present study showed a higher SR in Her-2-negative breast cancer than in Her-2-positive breast cancer, which is similar to the finding of You et al 38 This higher SR in Her-2 negative lesions might be associated with higher-degree fibrosis and lower-degree necrosis. Of the 248 Her-2-negative masses, 61% were in grade 2, probably explaining why their stiffness was greater than that in Her-2-positive masses.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“… 43 , 44 In a murine model, Chamming’s et al 40 confirmed a negative correlation between stiffness and necrosis and a positive correlation between stiffness and fibrosis. However, the present study showed a higher SR in Her-2-negative breast cancer than in Her-2-positive breast cancer, which is similar to the finding of You et al 38 This higher SR in Her-2 negative lesions might be associated with higher-degree fibrosis and lower-degree necrosis. Of the 248 Her-2-negative masses, 61% were in grade 2, probably explaining why their stiffness was greater than that in Her-2-positive masses.…”
Section: Discussionsupporting
confidence: 91%
“…The association between histological grade and sonoelastographic features remains controversial. Similar to those made by You et al and Lee et al, 38 , 39 this study showed that the SRs of grades 2 and 3 were greater than that of grade 1, but the SR of grade 3 was lower than that of grade 2. Chamming et al 40 suggested that necrosis, more in higher grades, was correlated with stiffness.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In our study, the elastogram characteristics were those expected, corroborating the malignancy of the tumors diagnosed by histology. These characteristics are similar to those described in women since they present a predominance of blue tones both in the visual color scale [22,[34][35][36][37] as well as observing a high strain ratio [24,[34][35][36]. In our work, we have not been able to make a comparison between benign and malignant mammary tumors because only one benign tumor was diagnosed compared to the 56 malignant neoplasms included in the study.…”
Section: Discussionsupporting
confidence: 75%